Cardiac and pulmonary findings in dysferlinopathy: A 3‐year, longitudinal study. Issue 5 (5th March 2022) - Moore, Ursula; Fernandez‐Torron, Roberto; Jacobs, Marni; Gordish‐Dressman, Heather; Diaz‐Manera, Jordi; James, Meredith K.; Mayhew, Anna G.; Harris, Elizabeth; Guglieri, Michela; Rufibach, Laura E.; Feng, Jia; Blamire, Andrew M.; et al.
Abstract: Introduction/Aims: There is debate about whether and to what extent either respiratory or cardiac dysfunction occurs in patients with dysferlinopathy. This study aimed to establish definitively whether dysfunction in either system is part of the dysferlinopathy phenotype. Methods: As part of the Jain Foundation's International Clinical Outcome Study (COS) for dysferlinopathy, objective measures of respiratory and cardiac function were collected twice, with a 3‐y interval between tests, in 188 genetically confirmed patients aged 11–86 y (53% female). Measures included forced vital capacity (FVC), electrocardiogram (ECG), and echocardiogram (echo). Results: Mean FVC was 90% predicted at baseline, decreasing to 88% at year 3. FVC was less than 80% predicted in 44 patients (24%) at baseline and 48 patients (30%) by year 3, including ambulant participants. ECGs showed P‐wave abnormalities indicative of delayed trans‐atrial conduction in 58% of patients at baseline, representing a risk for developing atrial flutter or fibrillation. The prevalence of impaired left ventricular function or hypertrophy was comparable to that in the general population. Discussion: These results demonstrate clinically significant respiratory impairment and abnormal atrial conduction in some patients with dysferlinopathy. Therefore, we recommend that annual or biannual follow‐up should include FVC measurement, enquiry about arrhythmia symptoms and peripheral pulse palpation to assess cardiac rhythm. However, periodic specialist cardiac review is probably not warranted unless prompted by symptoms or abnormal pulse findings.